EFEKTIVITAS PEMBERDAYAAN PETANI KOLAM MELALUI KELOMPOK BUDIDAYA IKAN UNTUK PENINGKATAN EKONOMI MASYARAKAT - Abdul Rahman; Sahudi Sahudi; Pahri Pahri (OIKONOMIKA: Jurnal Kajian Ekonomi dan Keuangan Syariah, 2020)
The phenomenon that occurs in East Koya that there is an empowerment program implemented by the Jayapura City Fisheries Department to Pond Farmers through the Fish Cultivation Group in East Koya, is the basis for researchers to conduct research onthe empowerment, the thing to be gained from this research is the form of empowerment provided and measure the effectiveness of this empowerment to pond farmers through the Fish Cultivation group. This thesis research is located in Koya Timur Village, Muara Tami District, Jayapura City. This study uses qualitative research with a case study approach that uses secondary data and primary data obtained through observation, interviews, and documentation techniques. Data analysis techniques carried out several stages of data reduction, data presentation, conclusions and data verification. The resultsof this study are a form of empowerment given to Pond farmers through the Fish Cultivation Group, such as the provision of fish seedlings, fertilizer, feed, water pumps and fish germination, besides that they are also given training in how to properly cultivatefish, counseling about fish farming activities and giving risk protection for fish farming business through an insurance card. and providing infrastructure such as irrigation or water irrigation. While seeing the effectiveness of this empowerment has beeneffective in the field, although it has not been entirely done using indicators of effectiveness, namely understanding the program, on target, on time, achieving goals and real change. One of these indicators is on time that hasn't been done in the field.